Bank activities and their risk. Does an optimal model exist in banking? - Hryckiewicz-Gontarczyk, Aneta (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
Why did the German and Swiss banks suffer severely from the mortgage crisis while the banks following the “originate–and–distribute” model were less affected by the mortgage crisis? Why were the Spanish banks hardly affected by the financial distress and banks from Central and Eastern Europe were not impacted at all? How profitable were all these institutions and what was their risk? The mortgage crisis has revealed that the general knowledge regarding the banks activities and their risk is notably limited. In addition, the recent literature provides ambiguous results on the impact of bank strategies on bank risk. By analyzing the most prevalent banking strategies observed before the mortgage crisis among 360 banks around the world, we demonstrate the presence of a wide heterogeneity in the banking strategies. These can be grouped into the originator, trader, neutral and traditional models. We also analyze how the specific banking strategies affect bank distress during the mortgage crisis. We determine that the riskiest banking model is for cases in which the banks specialize in trading and securitization. Yet, the least risky banks seem to be the banks engaged in traditional banking activities. However, our evidence suggests that a well– diversified, neutral model, allows banks to stay profitable without a significant risk increase effect
Argument Oeconomica, 2016, Nr 1 (36), s. 125-164
Keywords: bank risk; business models; bank regulation; financial crisis; banking stability